Manufacturing method of grain-oriented electrical steel sheet

JP7644338B2Active Publication Date: 2025-03-12NIPPON STEEL CORPORATION
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2021065944
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-04-08
Publication Date
2025-03-12
Estimated Expiration
2041-04-08

AI Technical Summary

Benefits of technology

【0011】 本発明によれば、曲率の異なるコイル内外周でのGoss方位への方位集積度の差が小さく(その結果、磁束密度の差が小さく)、高い磁束密度を有する方向性電磁鋼板の製造方法を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007644338000004
    Figure 0007644338000004
  • Figure 0007644338000005
    Figure 0007644338000005
  • Figure 0007644338000001
    Figure 0007644338000001
Patent Text Reader

Abstract

To provide a method for manufacturing a grain-oriented electromagnetic steel sheet having a high magnetic flux density, with a smaller difference in orientation integration degree to a Goss orientation at inner and outer peripheries of a coil with different curvatures, with regard to a high-temperature slab heating process.SOLUTION: A method for manufacturing a grain-oriented electromagnetic steel sheet includes a decarburization-annealing step of decarburization-annealing a cold rolled steel sheet having a prescribed chemical constitution to obtain a decarburization-annealed steel sheet. The decarburization-annealing step includes: a local heating process of heating a surface of the cold rolled steel sheet by irradiation with a laser beam satisfying a prescribed condition in an air atmosphere so that a heating part extends in a direction at an angle of 30 to 150° to a rolling direction and forms a shape of a plurality of lines located at an interval of 5 to 30 mm in the rolling direction; and a temperature rising process of heating-up the cold rolled steel sheet after the local heating process at an average heating rate of 80°C / sec. or more from a temperature region of 450°C or lower to a temperature region of 750 to 950°C being a decarburization-annealing temperature in a non-oxidative atmosphere.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a grain-oriented electrical steel sheet. [Background technology]

[0002] Grain-oriented electrical steel sheets are soft magnetic materials and are primarily used as iron core materials for transformers, and therefore require magnetic properties such as high magnetization characteristics and low core loss. Iron loss is the power loss consumed as thermal energy when an iron core is excited by an alternating magnetic field, and from the viewpoint of energy saving, it is desired that iron loss be as low as possible.

[0003] The biggest factor governing iron loss characteristics is magnetic flux density (for example, B8: magnetic flux density in a magnetic field of 800 A / m), and the higher the magnetic flux density, the lower the iron loss. In grain-oriented electrical steel sheets, to increase the magnetic flux density, the crystal orientation is generally concentrated in the GOSS orientation, which is good for magnetic properties, during the manufacturing process (increasing the degree of orientation concentration). Low iron loss is achieved by refining the magnetic domain structure of grain-oriented electrical steel sheets, which have a high magnetic flux density. In order to increase the degree of orientation concentration in the GOSS orientation, a high-temperature, long-term finish annealing is usually performed. By performing the finish annealing, the longitudinal direction of the steel sheet, which has good magnetic properties, is aligned. <100> The direction of the steel plate is <110> As the "Goss orientation grains" grow to a size on the order of centimeters while encroaching on the surrounding crystal grains, the crystal orientation becomes aligned (the degree of orientation accumulation increases). Conventional techniques for improving the degree of orientation concentration in the GOSS orientation increase the selective growth of GOSS-oriented grains during final annealing while at the same time reducing the frequency of secondary recrystallization, resulting in larger diameter grains.

[0004] However, in the manufacture of grain-oriented electrical steel sheets, the finish annealing is performed in the coiled state. In other words, the secondary recrystallized grains grow in a state where the steel sheet has a certain curvature. Therefore, when the steel sheet is unwound from the coiled state and made flat, continuous deviations in the crystal orientation occur inside the grains according to the curvature of the coil. This deviation causes the easy axis of magnetization, <100> As a result, the magnetic flux density decreases and iron loss increases. Such deviation becomes larger as the grain size of the secondary recrystallized grains in the longitudinal direction of the coil increases and as the curvature of the coil increases (the radius of curvature decreases). As described above, with conventional technology, when trying to increase the degree of orientation concentration in the Goss orientation, the grain size of the secondary recrystallized grains increases. Therefore, in order to reduce iron loss throughout the entire length of the coil, a manufacturing method is needed that resolves the trade-off between increasing the degree of orientation concentration in the Goss orientation and reducing the diameter of the secondary recrystallized grains.

[0005] To address such problems, Patent Documents 1 to 4 disclose a method in which grooves are provided in a steel sheet to divide crystal grains and shorten the length of secondary recrystallized grains in the rolling direction. Moreover, Patent Documents 5 and 6 disclose that heat treatment by laser beam irradiation is performed before and after the decarburization annealing step to divide the crystal grains of the product. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2011-208196 A [Patent Document 2] JP 2002-294416 A [Patent Document 3] International Publication No. 2012 / 033197 [Patent Document 4] Japanese Patent Application Publication No. 7-268474 [Patent Document 5] International Publication No. 2012 / 014290 [Patent Document 6] Japanese Patent Application Publication No. 2-258928 Summary of the Invention [Problem to be solved by the invention]

[0007] However, although the techniques of providing grooves as described in Patent Documents 1 to 4 can certainly control the crystal grain size, the productivity of forming the grooves is low. In addition, the grooves cause a problem of a decrease in the space factor when the material is formed into a transformer. Furthermore, the techniques of dividing crystal grains by irradiating a laser beam as in Patent Documents 5 and 6 have a problem that in the high-temperature slab heating process in which an inhibitor that controls secondary recrystallization is created in the hot rolling process or hot-rolled sheet annealing process prior to the decarburization annealing process, crystal orientation grains (abnormal grains) with inferior magnetic properties are generated in the laser beam irradiated area. In other words, even if the grain boundaries of secondary recrystallized grains can be formed in the vicinity of the laser beam irradiated area, the presence of these abnormal grains deteriorates the magnetic flux density, making it difficult to achieve low iron loss.

[0008] The present disclosure has been made in view of the above problems, and an object of the present disclosure is to provide a method for producing a grain-oriented electrical steel sheet that is based on a high-temperature slab heating process, has a small difference in the degree of orientation concentration in the Goss orientation between the inner and outer periphery of a coil having different curvatures, and has a high magnetic flux density. [Means for solving the problem]

[0009] As mentioned above, in the past, efforts were made to improve the degree of orientation concentration in the GOSS orientation by uniformly controlling the structure and precipitates over the entire length and width of the coil through adjustments to the chemical composition and thermomechanical treatment conditions. However, at the same time, the secondary recrystallized grains became larger in diameter, resulting in a difference in the degree of orientation concentration between the inner and outer periphery of the coil, and a high magnetic flux density could not be obtained at the inner periphery of the coil. In particular, in grain-oriented electrical steel sheets manufactured using a high-temperature slab heating process, precipitates (inhibitors) such as AlN and MnS that control secondary recrystallization are created in the hot rolling and hot-rolled sheet annealing processes. Therefore, if excessive heat treatment is performed in subsequent processes (for example, after the cold rolling process), such as by irradiating with a laser beam, the precipitates created in the previous process will coarsen, causing problems in the control of secondary recrystallization and resulting in abnormal grains. Therefore, in order to simultaneously achieve an improvement in the degree of orientation accumulation in the Goss orientation and a reduction in the diameter of the secondary recrystallized grains, and to reduce the difference in the degree of orientation accumulation between the inner and outer periphery of the coil, the inventors focused on localized heat treatment using a laser beam and conducted extensive research into the possibility of a material design that deviates from the material balance of the conventional structure, precipitates, etc. described above. As a result of the inventors' research, they found that by performing localized heat treatment (linear heating) on ​​steel sheet under specified conditions, it is possible to achieve both improved orientation concentration in the GOSS orientation and a smaller diameter of secondary recrystallization, even in a high-temperature slab heating process, and to produce a grain-oriented electrical steel sheet with a small difference in orientation concentration between the inner and outer periphery of the coil and high magnetic flux density on both the inner and outer periphery.

[0010] The present disclosure has been made based on the above findings. The gist of the present disclosure is as follows. [1] In mass%, C: 0.01~0.20%, Si: 2.0~4.5%, Mn: 0.01~0.30%, S: 0.01~0.05%, sol.Al: 0.01~0.05%, N: 0.001~0.0 20%, Cr:0~0.50%, Cu:0~0.50%, Ni:0~0.50%, Se:0~0.030%, Sn:0~0.50%, Sb:0~0.15%, Mo:0~0.20%, P:0~0.15 %, and V: 0 to 0.15%, with the balance being Fe and impurities, is heated to 1280°C or higher, and the heated slab is hot-rolled to obtain a hot-rolled steel sheet; a hot-rolled sheet annealing process is performed to anneal the hot-rolled steel sheet; a cold rolling process is performed to cold-roll the hot-rolled steel sheet after the hot-rolled sheet annealing process to obtain a cold-rolled steel sheet; and a decarburization annealing process is performed on the cold-rolled steel sheet to obtain a decarburization annealed steel sheet. and a finish annealing process of subjecting the decarburization-annealed steel sheet to finish annealing, the decarburization annealing process comprising: a local heating process of heating the surface of the cold-rolled steel sheet by irradiation with a laser beam in an air atmosphere so that heated parts are in the form of a plurality of lines extending in a direction at an angle of 30 to 150° with respect to the rolling direction and positioned at intervals of 5 to 30 mm in the rolling direction; and a heating process of heating the cold-rolled steel sheet after the local heating process in a non-oxidizing atmosphere from a temperature range of 450°C or less to a temperature range of 750 to 950°C, which is the decarburization annealing temperature, at an average heating rate of 80°C / sec or more, the average intensity of the laser beam being P in W, the focal diameter of the focal spot in the rolling direction being Dl in mm, the scanning speed of the laser beam being Vc in mm / sec, and the instantaneous input energy expressed as 4 / π×P / (Dl×Vc) being J / mm 2 and Up satisfies the following formulas (1) and (2): 0.2 ≦ Dl ≦ 1.0 (1) 0.5 ≦ Up ≦ 5.0 (2) [2] The chemical composition of the slab is Cr: 0.01 to 0.50%, Cu: 0.01 to 0.50%, Ni: 0.01 to 0.50%, Se: 0.005-0.030%, Sn: 0.01 to 0.50%, Sb: 0.01 to 0.15%, Mo: 0.01 to 0.20%, P: 0.01-0.15%, and V: 0.01-0.15%, The method for producing a grain-oriented electrical steel sheet according to [1], comprising one or more selected from the group consisting of: Effect of the Invention

[0011] According to the present invention, it is possible to provide a manufacturing method for grain-oriented electrical steel sheet having a small difference in the degree of orientation concentration in the Goss orientation between the inner and outer periphery of a coil having different curvatures (as a result, a small difference in magnetic flux density) and thus a high magnetic flux density. [Brief description of the drawings]

[0012] [Figure 1] FIG. 2 is a diagram showing an example of a cold-rolled steel sheet on which a linear heating portion is formed. [Diagram 2] 4A and 4B are diagrams for explaining a focused diameter and a scanning speed of a laser beam. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] A method for producing a grain-oriented electrical steel sheet according to an embodiment of the present disclosure (a method for producing a grain-oriented electrical steel sheet according to the present embodiment) will be described. The method for producing a grain-oriented electrical steel sheet according to this embodiment includes the following steps. (I) a hot rolling process in which a slab having a predetermined chemical composition is heated to 1280°C or higher and the heated slab is hot rolled to obtain a hot rolled steel sheet; (II) a hot-rolled sheet annealing step of annealing the hot-rolled steel sheet; (III) a cold rolling step of cold rolling the hot-rolled steel sheet after the hot-rolled sheet annealing step to obtain a cold-rolled steel sheet; (IV) a decarburization annealing step of subjecting the cold-rolled steel sheet to decarburization annealing to obtain a decarburization annealed steel sheet; and (V) A finish annealing process for subjecting the decarburized annealed steel sheet to finish annealing. Each step will be described below. For steps or conditions that are not described, known steps and conditions can be applied.

[0014] <Hot rolling process> In the hot rolling process, a slab having a chemical composition described below is heated to 1280° C. or higher, and the heated slab is hot rolled to produce a hot-rolled steel sheet. If the heating temperature is less than 1280°C, the inclusions formed in the slab cannot be dissolved, and the inhibitor is not sufficiently formed in the hot rolling process and the hot-rolled sheet annealing process described later. Therefore, the slab heating temperature is set to 1280°C or higher. Although there is no upper limit for the slab heating temperature, if the slab is heated at a temperature exceeding 1450°C, the slab melts, making hot rolling difficult. Therefore, the slab heating temperature is preferably 1450°C or lower. The hot rolling conditions are not particularly limited and may be appropriately set based on the desired properties. The thickness of the hot rolled steel sheet obtained by hot rolling is preferably within a range of 1.0 mm to 4.0 mm, for example.

[0015] [Chemical composition of slabs] In order to obtain favorable magnetic properties for grain-oriented electrical steel sheet, the chemical composition of the slab to be subjected to hot rolling is set to the following range. In the following description, unless otherwise specified, "%" stands for "mass %".

[0016] C: 0.01 to 0.20% C (carbon) is an element that shows an improvement effect of magnetic flux density, but if the C content of the slab exceeds 0.20%, the productivity in the decarburization annealing process decreases. In addition, if the C content of the slab is high and decarburization is insufficient, the steel undergoes phase transformation in secondary recrystallization annealing (i.e., finish annealing), and secondary recrystallization does not proceed sufficiently, so that good magnetic flux density and low iron loss cannot be obtained, or magnetic properties deteriorate due to magnetic aging. Therefore, the C content of the slab is set to 0.20% or less. The lower the C content, the more favorable it is for productivity and iron loss reduction. From the viewpoint of productivity and iron loss reduction, the C content is preferably 0.15% or less, more preferably 0.10% or less. On the other hand, if the C content of the slab is less than 0.01%, the effect of improving the magnetic flux density cannot be obtained. Therefore, the C content of the slab is set to 0.01% or more. The C content is preferably 0.04% or more, and more preferably 0.06% or more.

[0017] Silicon: 2.0 to 4.5% Silicon (Si) is an extremely effective element for increasing the electrical resistance (resistivity) of steel and reducing eddy current loss, which constitutes part of iron loss. If the Si content of the slab is less than 2.0%, the resistivity is small and eddy current loss cannot be reduced sufficiently. In addition, the steel undergoes phase transformation during secondary recrystallization annealing, and secondary recrystallization does not progress sufficiently, making it difficult to obtain good magnetic flux density and low iron loss. Therefore, the Si content of the slab is set to 2.0% or more. The Si content of the slab is preferably 2.1% or more, and more preferably 2.2% or more. On the other hand, if the Si content exceeds 4.5%, the steel sheet becomes embrittled and the sheet passing property during the manufacturing process is significantly deteriorated. Therefore, the Si content of the slab is set to 4.5% or less. The Si content of the slab is preferably 4.4% or less, and more preferably 4.2% or less.

[0018] Mn: 0.01 to 0.30% Mn (manganese) is an important element that forms MnS, which is one of the main inhibitors. If the Mn content of the slab is less than 0.01%, the absolute amount of MnS required to cause secondary recrystallization is insufficient. Therefore, the Mn content of the slab is set to 0.01% or more. The Mn content is preferably 0.03% or more, and more preferably 0.06% or more. On the other hand, if the Mn content of the slab exceeds 0.30%, the steel undergoes phase transformation during secondary recrystallization annealing, and secondary recrystallization does not proceed sufficiently, making it difficult to obtain good magnetic flux density and low core loss. Therefore, the Mn content of the slab is set to 0.30% or less. The Mn content is preferably 0.28% or less, and more preferably 0.26% or less.

[0019] S: 0.01 to 0.05% S (sulfur) is an important element that reacts with the above-mentioned Mn to form MnS, which is an inhibitor. If the S content of the slab is less than 0.01%, a sufficient inhibitor is not formed. Therefore, the S content of the slab is set to 0.01% or more. The S content is preferably 0.02% or more. On the other hand, if the S content of the slab exceeds 0.05%, it causes hot brittleness and makes hot rolling extremely difficult. Therefore, the S content of the slab is set to 0.05% or less. The S content is preferably 0.04% or less, and more preferably 0.03% or less.

[0020] Sol.Al: 0.01-0.05% Sol.Al (acid-soluble aluminum) is a constituent element of the main inhibitor among compounds called inhibitors that affect secondary recrystallization in grain-oriented electrical steel sheets, and is an essential element in the base steel sheet according to this embodiment from the viewpoint of secondary recrystallization. If the sol.Al content of the slab is less than 0.01%, AlN that functions as an inhibitor is not generated sufficiently, and secondary recrystallization becomes insufficient. Therefore, the sol.Al content is set to 0.01% or more. The sol.Al content is preferably 0.02% or more. On the other hand, if the sol.Al content exceeds 0.05%, AlN that functions as an inhibitor is not generated sufficiently, and secondary recrystallization becomes insufficient. Therefore, the sol.Al content is set to 0.05% or less. The sol.Al content is preferably 0.04% or less, and more preferably 0.03% or less.

[0021] N: 0.001 to 0.020% N (nitrogen) is an element that reacts with the above-mentioned acid-soluble Al to form AlN that functions as an inhibitor. In order to form a sufficient amount of AlN that functions as an inhibitor, the N content is set to 0.001% or more. The N content is preferably 0.005% or more. On the other hand, if the N content exceeds 0.020%, blisters (voids) are generated in the steel sheet during cold rolling, and the strength of the steel sheet increases, resulting in poor sheet passing properties during production. Therefore, the N content of the slab is set to 0.020% or less. The N content is preferably 0.015% or less, and more preferably 0.010% or less.

[0022] Cr: 0~0.50% Cr (chromium) is an element that contributes to increasing the Goss orientation occupancy rate in the secondary recrystallized structure, improving the magnetic properties, and also contributing to improving the adhesion of the glass coating, similar to Sn and Cu described later. Therefore, Cr may be contained. In order to obtain the above effects, the Cr content is preferably 0.01% or more, more preferably 0.02% or more, and even more preferably 0.03% or more. On the other hand, if the Cr content exceeds 0.50%, Cr oxides are formed and the magnetic properties deteriorate. Therefore, the Cr content is set to 0.50% or less. The Cr content is preferably 0.30% or less, and more preferably 0.10% or less.

[0023] Cu: 0-0.50% Cu (copper) is an element that contributes to increasing the Goss orientation occupancy rate in the secondary recrystallized structure and also contributes to improving the adhesion of the glass coating. Therefore, it may be contained. To obtain the above effects, the Cu content is preferably 0.01% or more. The Cu content is more preferably 0.02% or more, and further preferably 0.03% or more. On the other hand, if the Cu content exceeds 0.50%, the steel sheet becomes embrittled during hot rolling. Therefore, the Cu content of the slab is set to 0.50% or less. The Cu content is preferably 0.30% or less, and more preferably 0.10% or less.

[0024] Ni: 0 to 0.50% Ni (nickel) is an element effective in increasing electrical resistance and reducing iron loss. Ni is also an element effective in controlling the metal structure of the hot-rolled steel sheet and improving the magnetic properties. Therefore, Ni may be contained. To obtain the above effects, the Ni content is preferably 0.01% or more. The Ni content is more preferably 0.02% or more. On the other hand, if the Ni content exceeds 0.50%, the secondary recrystallization may become unstable. Therefore, the Ni content is set to 0.50% or less, and preferably to 0.30% or less.

[0025] Se: 0 to 0.030% Se (selenium) is an element that has a magnetic property improving effect. Therefore, it may be contained. When Se is contained, it is preferable that the Se content is 0.005% or more in order to effectively exhibit the magnetic property improving effect. In consideration of achieving both magnetic properties and coating adhesion, the Se content is more preferably 0.010% or more. On the other hand, if the Se content exceeds 0.030%, the glass coating is significantly deteriorated. Therefore, the Se content is set to 0.030% or less. The Se content is preferably 0.025% or less, and more preferably 0.020% or less.

[0026] Sn: 0 to 0.50% Sn (tin) is an element that has a magnetic property improving effect. Therefore, it may be contained. When Sn is contained, it is preferable that the Sn content is 0.01% or more in order to effectively exhibit the magnetic property improving effect. In consideration of achieving both magnetic properties and coating adhesion, the Sn content is preferably 0.02% or more, and more preferably 0.03% or more. On the other hand, if the Sn content exceeds 0.50%, the glass coating deteriorates significantly and sufficient tension for magnetic domain refinement is not obtained, resulting in deterioration of core loss characteristics. Therefore, the Sn content is set to 0.50% or less. The Sn content is preferably 0.30% or less, and more preferably 0.20% or less.

[0027] Sb: 0 to 0.15% Sb (antimony) is an element that has a magnetic property improving effect. Therefore, it may be contained. When Sb is contained, the content is preferably 0.01% or more in order to effectively exhibit the magnetic property improving effect. The Sb content is more preferably 0.02% or more. On the other hand, if the Sb content exceeds 0.15%, the adhesion of the glass coating deteriorates. Therefore, the Sb content is set to 0.15% or less. The Sb content is preferably 0.10% or less.

[0028] Mo: 0 to 0.20% Mo (molybdenum) is an element that has a magnetic property improving effect. Therefore, it may be contained. When Mo is contained, it is preferable that the Mo content is 0.01% or more in order to effectively exhibit the magnetic property improving effect. The Mo content is more preferably 0.02% or more, and further preferably 0.03% or more. On the other hand, if the Mo content exceeds 0.20%, the cold rolling property deteriorates and may lead to fracture. Therefore, the Mo content is set to 0.20% or less. The Mo content is preferably 0.10% or less, and more preferably 0.08% or less.

[0029] P: 0 to 0.15% P (phosphorus) is an element that reduces workability in rolling. By setting the P content to 0.15% or less, it is possible to prevent the rolling workability from being excessively reduced, and to prevent breakage during manufacturing. From this viewpoint, the P content is set to 0.15% or less. The P content is preferably 0.10% or less, and more preferably 0.05% or less. The lower limit of the P content is not limited and may include 0%, but P is also an element that has the effect of improving the texture and magnetic properties. To obtain this effect, the P content may be 0.005% or more, or 0.01% or more.

[0030] V: 0 to 0.15% V (vanadium) is an effective element that functions as an inhibitor by bonding with N and C. Therefore, V may be contained. To obtain the above effects, the V content is preferably 0.01% or more, and more preferably 0.02% or more. On the other hand, if the V content exceeds 0.15%, the magnetic properties may deteriorate, so the V content is set to 0.15% or less. The V content is preferably 0.10% or less, and more preferably 0.05% or less.

[0031] Remainder: Fe and impurities The chemical composition of the slab used in the manufacturing method of the grain-oriented electrical steel sheet according to the present embodiment may contain the above-mentioned elements, with the balance being Fe and impurities. Here, the impurities refer to elements that are mixed in from raw materials such as ores and scraps or from the manufacturing environment when the base steel sheet is industrially manufactured, and that are allowed to be contained in an amount that does not adversely affect the function of the grain-oriented electrical steel sheet according to the present embodiment.

[0032] <Hot-rolled sheet annealing process> The hot-rolled steel sheet annealing process is a process of annealing the hot-rolled steel sheet manufactured through the hot rolling process. By carrying out such annealing treatment, recrystallization occurs in the steel sheet structure, making it possible to realize good magnetic properties. In the hot-rolled steel sheet annealing process of this embodiment, the hot-rolled steel sheet manufactured through the hot rolling process may be annealed according to a known method. The means for heating the hot-rolled steel sheet during annealing is not particularly limited, and known heating methods can be adopted. The annealing conditions are also not particularly limited, but for example, the hot-rolled steel sheet may be annealed in a temperature range of 900 to 1200°C for 10 seconds to 5 minutes.

[0033] <Cold rolling process> In the cold rolling process, the hot-rolled steel sheet after the hot-rolled sheet annealing process is subjected to cold rolling including multiple passes to obtain a cold-rolled steel sheet. The cold rolling may be a single cold rolling, or may be multiple cold rolling passes with intermediate annealing interposed therebetween, with the cold rolling interrupted before the final pass of the cold rolling process and at least one or two intermediate annealings being performed before the final pass of the cold rolling process. When intermediate annealing is performed, it is preferable to hold the steel sheet at a temperature of 1000 to 1200° C. for 5 to 180 seconds. The annealing atmosphere is not particularly limited. In consideration of the manufacturing cost, it is preferable to perform intermediate annealing three times or less. Furthermore, before the cold rolling step, the surface of the hot-rolled steel sheet may be subjected to pickling under known conditions.

[0034] <Decarburization annealing process> In the decarburization annealing step, the cold-rolled steel sheet is subjected to decarburization annealing to obtain a decarburization annealed steel sheet. In the decarburization annealing, the cold-rolled steel sheet is subjected to primary recrystallization and C, which adversely affects magnetic properties, is removed from the steel sheet. In the manufacturing method of the grain-oriented electrical steel sheet according to the present embodiment, however, the steel sheet is locally heated before being heated to the annealing temperature. That is, the decarburization annealing process includes a local heating process in which the surface of the cold-rolled steel sheet is heated in an air atmosphere so that the heated parts are in the form of multiple lines extending in a direction at an angle of 30 to 150° to the rolling direction (sheet passing direction) and positioned at intervals of 5 to 30 mm in the rolling direction, and a heating process in which the cold-rolled steel sheet after the local heating process is heated in a non-oxidizing atmosphere from a temperature range of 450°C or less to a temperature range of 750 to 950°C, which is the decarburization annealing temperature, at an average heating rate of 80°C / sec or more.

[0035] [Local heating process] In the localized heating process, the surface of the cold-rolled steel sheet is heated in an air atmosphere so that the heated parts extend in a direction that forms an angle of 30 to 150° with respect to the rolling direction (a direction that is ±60° with respect to a direction perpendicular to the rolling direction) and form multiple lines spaced at intervals of 5 to 30 mm in the rolling direction. The cold-rolled steel sheet after the localized heating has linear heated parts as shown in FIG. 1. In the manufacturing method of the grain-oriented electrical steel sheet according to the present embodiment, the steel sheet is subjected to linear heating to increase the grain size in the heated portion. The portion with the increased grain size acts as a barrier to the growth of secondary recrystallized grains during the subsequent finish annealing process, suppressing the growth of the secondary recrystallized grains. Therefore, by repeatedly applying linear heating extending in a direction intersecting the rolling direction at a predetermined interval in the rolling direction (forming multiple heated portions), the length of the secondary recrystallized grains in the rolling direction can be reduced.

[0036] When the extension direction of the linear heated portion is less than 30° or more than 150° to the rolling direction (close to parallel to the rolling direction), the length of the secondary recrystallized grains in the rolling direction cannot be reduced. Furthermore, if the interval between the linear heating parts exceeds 30 mm, the effect of reducing the length of the secondary recrystallized grains in the rolling direction is small. On the other hand, if the interval between the linear heating parts is less than 5 mm, the coarse grains become excessive, causing secondary recrystallization defects (the degree of accumulation in the Goss orientation decreases). The intervals between the linear heating parts may be approximately equal, but the intervals between adjacent linear heating parts may be controlled to be different as long as they are within the range of the intervals between the linear heating parts described above. For example, in the outer periphery with a large curvature, the effect of the length of the secondary recrystallized grains in the rolling direction on the Goss concentration is small, so the intervals between the heating parts may be made wider than in the inner periphery with a small curvature. The width of the linear heating portion is preferably 0.2 to 1.0 mm. If it is less than 0.2 mm, the heating portion is small, and the function as an obstacle to the growth of secondary recrystallization is low, and there is a concern that the effect of reducing the length of the secondary recrystallized grains in the rolling direction is not obtained. On the other hand, if it exceeds 1.0 mm, there is an effect of reducing the length of the secondary recrystallized grains in the rolling direction, but coarse grains in the heating portion remain even after finish annealing, and there is a concern that the magnetic properties are deteriorated. Furthermore, the length of the linear heating portion is not limited, but it is preferable that the heating portion be formed over the entire width of the steel sheet, or over the entire width excluding the edge portions.

[0037] Furthermore, local heating (formation of a linear heated portion) is performed by irradiating a laser beam, which allows localized heating and has little effect on the surroundings. When heating is performed by laser beam irradiation, the average intensity of the laser beam is P (W), the focal spot diameter in the rolling direction is Dl (mm), the scanning speed of the laser beam is Vc (mm / sec), and the instantaneous input energy expressed by 4 / π×P / (Dl×Vc) is Up (J / mm 2 ), the laser beam is irradiated under conditions that satisfy the following expressions (1) and (2). The focused diameter Dl is the diameter shown in Fig. 2, and the scanning speed Vc is the speed in the direction (extension direction of the linear heating part) shown in Fig. 2. The scanning speed Vc is determined from the sheet passing speed and the scanning speed of the laser beam in the width direction. 0.2 ≦ Dl ≦ 1.0 (1) 0.5 ≦ Up ≦ 5.0 (2) By satisfying the conditions of formulas (1) and (2), the length of the secondary recrystallized grains in the rolling direction can be reduced, and the difference in the degree of orientation accumulation in the Goss orientation at the inner and outer periphery of the coil with different curvatures is reduced. If formulas (1) and (2) are not satisfied, sufficient effects cannot be obtained.

[0038] [Temperature rise process] In the heating process, the cold-rolled steel sheet after the local heating process is heated in a non-oxidizing atmosphere from a temperature range of 450° C. or lower to a temperature range of 750 to 950° C., which is the decarburization annealing temperature, at an average heating rate of 80° C. / sec or higher. The above temperature rise promotes the nucleation of GOSS orientation grains. If the average heating rate in the above temperature range is less than 80°C / sec, the nucleation is insufficient and the grain size of the secondary recrystallized grains becomes large. In addition, when the secondary recrystallized grain size in the rolling direction is reduced by local heating, sufficient secondary recrystallized nuclei are required to completely cover the entire surface of the steel sheet with GOSS orientation, which is good for magnetic properties. Therefore, the average heating rate is preferably 160°C / sec or more, more preferably 240°C / sec or more. There is no upper limit to the heating rate, and it may be determined by the equipment capacity. For example, it is 2000°C / sec or less. Furthermore, if the atmosphere during heating is not a non-oxidizing atmosphere, a tight SiO2 film is formed on the surface layer of the steel sheet, causing poor decarburization and poor coating after final annealing. In this embodiment, the non-oxidizing atmosphere is a nitrogen atmosphere or a mixed atmosphere of nitrogen and hydrogen, and has a dew point of -50°C or more and 0°C or less. From the viewpoint of suppressing SiO2 generation and smoothly advancing decarburization, the dew point is preferably -5°C or less, or -10°C or less. From the viewpoint of smoothly advancing internal oxidation for ease of process control, the dew point may be, for example, -40°C or more.

[0039] The annealing after the temperature is raised to 750 to 950°C during the temperature rise process is not limited, but for example, the oxidation degree (PH2O / PH2) in the annealing atmosphere (furnace atmosphere) may be set to 0.15 to 1.0, and the temperature may be held in that temperature range for 10 to 600 seconds.

[0040] <Finish annealing process> In the final annealing process, a predetermined annealing separator is applied to one or both sides of the decarburized annealed steel sheet obtained in the decarburization annealing process, and then the decarburized annealed steel sheet is subjected to final annealing. Final annealing is generally performed for a long time while the steel sheet is wound in a coil shape. Therefore, prior to the final annealing, an annealing separator is applied to the decarburized annealed steel sheet and dried in order to prevent seizure between the inside and outside of the coil winding. The annealing separator to be applied is one that contains MgO as its main component (e.g., 80% or more by weight). By using an annealing separator that contains MgO as its main component, a glass coating can be formed on the surface of the base steel sheet. If MgO is not the main component, the primary coating (glass coating) will not be formed. This is because the primary coating is an Mg2SiO4 or MgAl2O4 compound, and if MgO is not the main component, there will be a shortage of Mg, which is necessary for the formation reaction. The finish annealing may be performed, for example, in an atmospheric gas containing hydrogen and nitrogen by raising the temperature to 1150 to 1250° C. and annealing at that temperature for 10 to 60 hours. EXAMPLES

[0041] <Example 1> A slab containing, by mass%, C: 0.08%, Si: 3.3%, Mn: 0.08%, S: 0.02%, acid-soluble Al: 0.03%, N: 0.009%, with the balance being Fe and impurities, was heated to 1350°C and hot-rolled to obtain a 2.0 mm hot-rolled steel sheet. The obtained hot-rolled steel sheet was annealed at 1000° C. for 60 seconds (hot-rolled sheet annealing) to obtain a hot-rolled annealed steel sheet. The obtained hot-rolled and annealed steel sheet was cold-rolled to obtain a cold-rolled steel sheet having a thickness of 0.2 mm. A cold-rolled steel sheet was irradiated with a laser beam in an air atmosphere under the conditions shown in Tables 1A and 1B so that the heated parts extended at an angle of 85° with respect to the rolling direction (a direction inclined by 5° from a direction perpendicular to the rolling direction) and formed multiple straight lines spaced at 10 mm intervals in the rolling direction, and then heated in a nitrogen / hydrogen mixed atmosphere with a dew point of -30°C from a temperature range of 450°C or less to a temperature range of 750 to 950°C at an average heating rate as shown in Tables 1A and 1B. The width of the heated parts in the rolling direction matched the focused beam diameter Dl in the rolling direction and was in the range of 0.2 to 0.6 mm. After heating, the oxidation degree (PH2O / PH2) in the annealing atmosphere (furnace atmosphere) was set to 0.6, and the steel was held at 750 to 950°C for 10 to 600 seconds to perform decarburization annealing, thereby obtaining a decarburization annealed steel sheet. The decarburized annealed steel sheet was wound into a coil and subjected to finish annealing in the coil state. In the finish annealing, the temperature was raised to 1150°C and held at that temperature range for 20 hours. As a result, a grain-oriented electrical steel sheet was obtained.

[0042] After the finish annealing, samples for measuring magnetic properties, each measuring 60 mm x 300 mm, were taken from a position on the coil having a radius of curvature of 300 mm corresponding to the inner circumference of the coil and a position on the coil having a radius of curvature of 800 mm corresponding to the outer circumference of the coil. The magnetic flux density of this sample was measured in accordance with JIS C2556:2015. The results are shown in Tables 1A and 1B.

[0043] [Table 1A]

[0044] [Table 1B]

[0045] As can be seen from Tables 1A and 1B, in the examples of the invention in which the laser beam irradiation conditions and the average heating rate from 450°C or less to the decarburization annealing temperature were within the range of the present invention, the magnetic flux density on both the inner and outer periphery of the coil was 1.92 T or more, and the difference in magnetic flux density between the inner and outer periphery was reduced to 0.00 T. On the other hand, in the comparative examples in which at least one of the laser beam irradiation conditions and the average heating rate from 450° C. or less to the decarburization annealing temperature was outside the range of the present invention, the magnetic flux density was less than 1.92 T and / or the difference in magnetic flux density was 0.01 T or more.

[0046] <Example 2> A slab having the chemical composition shown in Table 2 (unit: mass %, balance: Fe and impurities) was heated to 1350° C. and hot rolled to obtain a hot-rolled steel sheet of 2.0 mm. The obtained hot-rolled steel sheet was annealed. The obtained hot-rolled and annealed steel sheet was cold-rolled to obtain a cold-rolled steel sheet having a thickness of 0.2 mm. The heating zone was set at an angle of 85° to the rolling direction (a direction inclined by 5° from the direction perpendicular to the rolling direction) on a cold-rolled steel sheet, and was arranged in multiple straight lines at intervals of 10 mm in the rolling direction. The focusing diameter in the rolling direction (Dl) was 0.6 mm, the output / scanning speed (P / Vc) was 0.95 J / mm, and the instantaneous input energy (Up) was 2.0 J / mm in an air atmosphere. 2 The laser beam was irradiated under the following conditions. Then, the steel was heated to the decarburization annealing temperature of 750 to 950°C at an average heating rate of 200°C / s from below 450°C to the decarburization annealing temperature in a nitrogen / hydrogen mixed atmosphere with a dew point of -30°C. After heating, the oxidation degree (PH2O / PH2) in the annealing atmosphere (furnace atmosphere) was set to 0.6, and the steel was held at 750 to 950°C for 10 to 600 seconds to perform decarburization annealing, thereby obtaining a decarburization annealed steel sheet. The decarburized annealed steel sheet was wound into a coil and subjected to finish annealing in the coil state. In the finish annealing, the temperature was raised to 1150°C and held at that temperature range for 20 hours. As a result, a grain-oriented electrical steel sheet was obtained.

[0047] After the finish annealing, samples of 60×300 mm for measuring magnetic properties were taken from a position with a curvature radius of 300 mm corresponding to the inner circumference of the coil and a position with a curvature radius of 800 mm corresponding to the outer circumference of the coil. The magnetic flux density of this sample was measured in accordance with JIS C2556:2015. The results are shown in Table 2.

[0048] [Table 2]

[0049] As can be seen from Table 2, in all examples, the magnetic flux density on the inner periphery and outer periphery of the coil was 1.92T or more, and the difference between them was 0.00T.

Claims

1. A hot rolling process in which a slab having a chemical composition containing, in mass%, C: 0.01 to 0.20%, Si: 2.0 to 4.5%, Mn: 0.01 to 0.30%, S: 0.01 to 0.05%, sol. Al: 0.01 to 0.05%, N: 0.001 to 0.020%, Cr: 0 to 0.50%, Cu: 0 to 0.50%, Ni: 0 to 0.50%, Se: 0 to 0.030%, Sn: 0 to 0.50%, Sb: 0 to 0.15%, Mo: 0 to 0.20%, P: 0 to 0.15%, and V: 0 to 0.15%, with the balance being Fe and impurities, is heated to 1280 ° C. or higher, and the heated slab is hot-rolled to obtain a hot-rolled steel sheet; A hot-rolled steel sheet annealing process for annealing the hot-rolled steel sheet; A cold rolling process in which cold rolling is performed on the hot-rolled steel sheet after the hot-rolled sheet annealing process to obtain a cold-rolled steel sheet; a decarburization annealing step of subjecting the cold-rolled steel sheet to decarburization annealing to obtain a decarburization annealed steel sheet; A finish annealing process for performing finish annealing on the decarburized annealed steel sheet; Including, The decarburization annealing step includes: a local heating process of heating the surface of the cold-rolled steel sheet by irradiating the surface with a laser beam in an air atmosphere so that the heated portions are in the form of a plurality of lines extending in a direction at an angle of 30 to 150° to the rolling direction and positioned at intervals of 5 to 30 mm in the rolling direction; A heating process in which the cold-rolled steel sheet after the local heating process is heated in a non-oxidizing atmosphere from a temperature range of 450° C. or less to a temperature range of 750 to 950° C., which is the decarburization annealing temperature, at an average heating rate of 80° C. / sec or more. Including, The average intensity of the laser beam is P in W, the focal diameter of the focal spot in the rolling direction is Dl in mm, the scanning speed of the laser beam is Vc in mm / sec, and the instantaneous input energy expressed by 4 / π×P / (Dl×Vc) is J / mm 2 When Up is used, the following formulas (1) and (2) are satisfied. A method for producing a grain-oriented electrical steel sheet comprising the steps of: 0.2 ≦ Dl ≦ 1.0 (1) 0.5≦Up≦5.0 (2)

2. The chemical composition of the slab is Cr: 0.01-0.50%, Cu: 0.01 to 0.50%, Ni: 0.01-0.50%, Se: 0.005-0.030%, Sn: 0.01-0.50%, Sb: 0.01 to 0.15%, Mo: 0.01-0.20%, P: 0.01 to 0.15%, and V: 0.01-0.15%, Contains one or more selected from the group consisting of The method for producing a grain-oriented electrical steel sheet according to claim 1 .

Citation Information

Patent Citations

  • Method for improving magnetic performance of silicon steel sheet through laser indented oriented silicon steel cold-rolled sheet

    CN105463172A

  • JP1975137819A

  • Production of grain-oriented silicon steel sheet having controlled secondary recrystallized grain boundary

    JP1990258928A

  • Grain oriented silicon steel sheet with low iron loss

    JP1995268474A

  • Grain-oriented electro magnetic steel sheet with low core loss, and manufacturing method and manufacturing apparatus therefor

    JP2002294416A